Business Development Strategy Through SWOT Analysis and Human Resource Management in Food and Beverage Industry: A Case Study of XO Cafe Restaurant & Bar - Kolondam, Arifmanuel; Paendong, Melky; Maramis, Diana; Joroh, Adelaida (Universitas Diponegoro, 2025)
This research delves into the strategic landscape of XO Cafe Restaurant & Bar, employing a SWOT analysis to dissect its internal and external factors. Questionnaires distributed to 38 customers and 15 employees, combined with observational data, formed the basis of this analysis. The study identified key strengths such as varied beverage offerings, satisfactory service, affordable pricing, strong customer loyalty, and well-trained staff. Conversely, weaknesses were noted in the limited food variety, room layout, and aesthetics. Opportunities for XO Cafe lie in its diverse beverage selection, potential for repeat business, and flexible pricing. However, the business faces threats from competition and competitor menu variations. To formulate effective marketing strategies, the research utilized IFAS and EFAS matrices and a quantitative SWOT matrix. The IFAS matrix highlighted that XO Cafe's strengths outweigh its weaknesses, with